The Influence of Motivation, Compensation on Employee Performance: Job Satisfaction as an Intervening Variable - Mochamad Edris; Joko Utomo; Agus Kurniawan (IJIP : Indonesian Journal of Islamic Psychology, 2024)
This study aims to determine the effect of motivation and rewards on employee performance, with job satisfaction as an intervening variable. This study uses a quantitative approach with 140 respondents using the hair formula. Data collection using a questionnaire Research Instrument Test using Convergence Validity, Average Variance Extracted (AVE), Discriminant Validity, and Construct Reliability. Data analysis using SEM (Structural Equation Modeling) Analysis. The results of the study are that (1) work motivation has a positive and significant effect on job satisfaction (0.028 <0.05), (2) independence has a positive and significant effect on job satisfaction (0.012 <0.05). (3) Work motivation has a positive and significant effect on employee performance (0.043 < 0.05) (4) Compensation has a positive and significant effect on employee performance (0.929 > 0.05) (5) Job satisfaction has a positive and significant effect on employee performance (0.000 < 0.05) (6) Motivation has a positive and significant effect on employee performance through job satisfaction (0.292 < 0.343) (7) Compensation has a positive and significant effect on employee performance through job satisfaction, (0.019 < 0.346)